Co-existence of Tropical Storms - RAGHAVAN, K. (MAUSAM, 1965)
Results of a climatological study of two or more tropical cyclones/depressions that occurred simultaneously over the sea (Bay of Bengal and Arabian Sea) and the land area (India, Pakistan, Burma and Ceylon) during the years 1923 to 1962 are presented. Not more than two storms exist at a time in the region and they are observed during the period June to December. There was no occasion when both the storm existed in the Arabian Sea or in the Bay of Bengal. The shortest distance apart between the co-existing storms was 1000 km. The line joining the centres of two co-existing storms was generally east-west. Statistics of the storms are presented in charts and tables.